Conduite d'approche in conduction aphasia: Which psycholinguistic and experimental variables drive it – A case study. - Gutiérrez-Cordero, Ismael; Torres-Prioris, María José; García-Orza, Javier (My University, 2023)
Conduite d’approche (CdA) is a classic repetitive behavior reported frequently in persons with conduction aphasia, however, relatively little is known about it, both at the brain and cognitive level (e.g., whether it is a self-correcting mechanism based on comprehension or rather on production, Nickels and Howard, 1995; Ueno and Lambon-Ralph, 2013). In this work we address which psycholinguistic and experimental variables boost the occurrence of CdAs and are involved in reaching a successful CdA. Here we study ANC, a 79-year-old male with high sociocultural level who suffers from a reproduction conduction aphasia that caused frequent CdAs.
Keywords: Afasia; Lenguaje - Trastornos; Aphasia; Word production; Interference